Evaluasi Risiko Musculoskeletal Disorders pada Pekerja Mebel dengan Metode REBA dan RULA Sebagai Dasar Inovasi Desain Meja Kerja - Dedy Iskandar; Sugina Sugina; Putri Septiani Lestari (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Raw material measuring activities in the furniture industry are commonly performed on the floor, forcing workers to maintain prolonged squatting, bending, and neck flexion postures that increase the risk of Musculoskeletal Disorders (MSDs). This study aimed to evaluate ergonomic risk using the Rapid Entire Body Assessment (REBA) and Rapid Upper Limb Assessment (RULA) methods as the basis for developing an ergonomic workbench design. A descriptive quantitative approach was employed through observation, interviews, documentation, work posture assessment, and anthropometric measurements of five workers. The results indicated a REBA score of 12 (Very High Risk) and a RULA score of 7 (Investigate and Implement Change). Based on these findings, an anthropometry-based ergonomic workbench was designed to improve working posture and increase production efficiency, reducing working time from 36 minutes to 23.5 minutes (34.7%). The proposed innovation is expected to reduce MSD risks while improving occupational safety, comfort, and productivity.